Analisis Evaluasi Pengalaman Pengguna Pada Aplikasi Viu Menggunakan Metode User Experience Questionnaire - Freda Desfita Artanti; Suprih Widodo (Journal of Information System Research (JOSH), 2025)
The advancement of information technology has transformed media consumption patterns in Indonesia, particularly with the emergence of streaming platforms like Viu. As one of Asia's popular Video on Demand (VoD) providers, Viu offers a variety of content such as Asian dramas, anime, and entertainment news. Despite its significant user base, reviews on Google Play Store reveal negative comments and low ratings, with a score of only 2.6 out of 5 stars. This highlights the need to evaluate user experience to identify the application's strengths and weaknesses. This study aims to analyze the user experience of the Viu application using the User Experience Questionnaire (UEQ), which encompasses six main scales: attractiveness, perspicuity, efficiency, dependability, stimulation, and novelty. Data was collected through an online questionnaire completed by 30 valid respondents and processed using UEQ Tools. The results show that the Perspicuity aspect achieved the highest average score (1.817), followed by Dependability (1.558), receiving a Good benchmark category, indicating that the application is easy to understand and provides good interaction control. Attractiveness, Efficiency, and Novelty were rated as Above Average, with average scores of 1.511, 1.383, and 0.983, respectively, reflecting a satisfactory user experience. However, Stimulation had the lowest score (0.950), below the benchmark average, indicating the need for improvement in providing enjoyment and motivation to users. Recommendations focus on feature innovation, enhanced interaction, and a more enjoyable user experience to meet the needs of Viu users in the digital era.